Phenotypic and molecular genetic analysis of Pyruvate Kinase deficiency in a Tunisian family - Jaouani Mouna (Egyptian Journal of Medical Human Genetics, 2016)
Pyruvate Kinase (PK) deficiency is the most frequent red cell enzymatic defect responsible for hereditary non-spherocytic hemolytic anemia. The disease has been studied in several ethnic groups. However, it is yet an unknown pathology in Tunisia. We report here, the phenotypic and molecular investigation of PK deficiency in a Tunisian family. This study was carried out on two Tunisian brothers and members of their family. Hematological, biochemical analysis and erythrocyte PK activity were performed. The molecular characterization was carried out by gene sequencing technique. The first patient died few hours after birth by hydrops fetalis, the second one presented with neonatal jaundice and severe anemia necessitating urgent blood transfusion. This severe clinical picture is the result of a homozygous mutation of PKLR gene at exon 8 (c.1079G>A; p.Cys360Tyr). Certainly, this research allowed us to correlate the clinical phenotype severity with the identified mutation. Moreover, this will help in understanding the etiology of unknown anemia in our country.